MiR-451 in Inflammatory Diseases: Molecular Mechanisms, Biomarkers, and Therapeutic Applications—A Comprehensive Review Beyond Oncology - Fei-Xiang Wang; Guo Mu; Zi-Hang Yu; Zhen-Shan Qin; Xing Zhao; Zu-An Shi; Xin Fan; Li Liu; Ye Chen; Jun Zhou (Current Issues in Molecular Biology)
MicroRNAs play crucial roles in regulating inflammatory responses and disease progression. Since its identification on chromosome 17q11.2 in 2005, miR-451 has emerged as a key regulator of multiple physiological and pathological processes. While its role in cancer has been extensively documented, accumulating evidence reveals miR-451’s broader significance in inflammatory conditions through the regulation of NF-κB, AMPK, and PI3K signaling pathways. This comprehensive review systematically analyzes miR-451’s multifaceted functions in inflammatory diseases, with particular focus on ischemia–reperfusion injury, arthritis, and acute organ injuries. We present compelling evidence for miR-451’s potential as a diagnostic biomarker, demonstrating its distinctive expression patterns across various biological specimens and disease states. Furthermore, we elucidate how miR-451 modulates inflammatory responses through the regulation of immune cell populations, including microglia activation, macrophage polarization, and neutrophil chemotaxis. By integrating current evidence and bioinformatic analyses, we establish a theoretical framework linking miR-451’s molecular mechanisms to its therapeutic applications. This review not only synthesizes the current understanding of miR-451 in inflammatory diseases but also provides critical insights for developing novel diagnostic tools and therapeutic strategies.